2000
DOI: 10.1046/j.1423-0410.2000.7930138.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus: Routes of Infection and Genotypes in a Cohort of Anti‐HCV‐Positive French Blood Donors

Abstract: In this population of anti-HCV-positive blood donors, nosocomial infection may be a route of HCV spread, but the main risk factor remains IVDU, particularly in young men. The transfusion policy will improve if predonation interviews of such young men are done with a specific and sensitive questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…We could determine the serotype of 55 (80.9%) of the 68 samples, which is comparable with some other studies reporting 81.2% and 83%, respectively [16,17]. Serotypes 1 and 3 were the most prevalent serotypes among the Belgian population, confirming another Belgian study [18] which enrolled fewer patients from Flanders, as well as other studies among the European population [19][20][21][22][23]. Although these studies established the genotype instead of the serotype, the results can be compared since results obtained through genotyping and serotyping carried out using SA1-6 show a good correlation [16,17,24].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We could determine the serotype of 55 (80.9%) of the 68 samples, which is comparable with some other studies reporting 81.2% and 83%, respectively [16,17]. Serotypes 1 and 3 were the most prevalent serotypes among the Belgian population, confirming another Belgian study [18] which enrolled fewer patients from Flanders, as well as other studies among the European population [19][20][21][22][23]. Although these studies established the genotype instead of the serotype, the results can be compared since results obtained through genotyping and serotyping carried out using SA1-6 show a good correlation [16,17,24].…”
Section: Discussionsupporting
confidence: 88%
“…We remark that another 33.3% (4/12) was sent by the same laboratory.Although this result is still higher than reported by others (e.g. 6.9% in France [21]), another Belgian study showed a prevalence of 10.6% [18]. The presence of cross-reactive antibodies probably also applies to type 6, which was not detected by genotyping, but in 14.7% by serotyping as part of multiple infections.…”
Section: Discussionmentioning
confidence: 53%
“…Nine cohort studies [100], [103], [105], [109], [113], [115], [117][119], and 21 cross-sectional studies tested HCV-RNA using PCR as a marker for chronic infection [81], [82], [90][99], [101], [102], [104], [106]–[108], [111], [112], [114], [116].…”
Section: Resultsmentioning
confidence: 99%
“…Cependant, 3 études ont montré la persistance de l'HP dans l'endoscope après le nettoyage et la désinfection, détecté par culture dans deux études et par PCR dans la 3 ème [50][51][52]. Risque infectieux lié à l'endoscopie digestive élevée d'explorations endoscopiques digestives parmi les sujets séropositifs pour le VHC par rapport aux sujets témoins [63][64][65][66][67][68][69][70]. Cependant, l'interprétation de ces études reste difficile car elles se basent uniquement sur l'interrogatoire pour exclure les autres voies de transmission du virus.…”
Section: Salmonellaunclassified